Indicadores energéticos de vacas lecheras a pastoreo en período de transición y lactancia temprana con alta o moderada condición corporal preparto (2014)
Blood markers for energy balance and milk production values, together with presentation of insulin resistance and ketosis were determined in grazing dairy cows during the periods of transition and early lactation and grouped according with their body condition score (BCS) before calving. The study was done in an experimental dairy herd, during the transitional period (3 weeks before to 3 weeks postcalving and early lactation, 4th to 8th weeks postcalving. Cows were distributed in two groups according to BCS (1 to 5 scale), high (=3.75; n=20) and moderate (3.00-3.50; n=28). Weekly variations of BCS, live body weight and blood markers for energy (non esterified fatty acids [NEFA], ß-OH-butyrate, glucose, cholesterol), protein (urea, albumin) and liver damage were determined. A glu- cose tolerance test and insulin resistance test were carry out during postcalving in nine cows of each group. Cows with high BCS at partum, compared to cows with moderate BCS at partum, had a larger blood lipid and glucose concentrations during precalving, produced more milk during the first three weeks postcalving and their blood glucose and cholesterol values at early lactation were higher, and also had a larger decrease in BCS. Presentation of negative energy balance and ketosis were similar in both groups of cows. However, excessive lipid mobilization (NEFA>0.40 mmol/L) and hyperglycaemia (>4.1 mmol/L) during precalving were the main risk factors for insulin resistance during the transition period. On the other hand hyperglycaemia precalving decreased the risk of a negative energy balance during lactation. It is concluded that dairy cows at pasture with high BCS precalving presents more lipid mobilization and have a higher glycaemia during the transitional period. Ketosis and insulin resistance presentations are independent of the BCS at calving, but are related to the lipid mobilization from the body fat stores to compensate the large demands for energy during lactation.